2016
DOI: 10.3390/ijms17040435
|View full text |Cite
|
Sign up to set email alerts
|

Knock-Down of Endogenous Bornavirus-Like Nucleoprotein 1 Inhibits Cell Growth and Induces Apoptosis in Human Oligodendroglia Cells

Abstract: Endogenous bornavirus-like nucleoprotein elements (EBLNs) have been discovered in the genomes of various animals including humans, whose functions have been seldom studied. To explore the biological functions of human EBLNs, we constructed a lentiviral vector expressing a short-hairpin RNA against human EBLN1, which successfully inhibited EBLN1 expression by above 80% in infected human oligodendroglia cells (OL cells). We found that EBLN1 silencing suppressed cell proliferation, induced G2/M phase arrest, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…Golgin45 was also demonstrated to interact with DNA (cytosine-5)-methyltransferase 3-like protein DNMT3L and AP-1 (9,10). Gene profile analysis found that Golgin45 expression was up-regulated in liver cells that responded to dengue virus infection (11), in transcription factor Gfi-1B (growth factor independence 1B) overexpressing leukemia cells (12), and in EBLN1 (Endogenous bornavirus-like nucleoprotein elements) silencing oligodendroglia cells (13), and it was reduced in hepatocellular carcinoma tissues (14). The exact role of Golgin45 still needs further confirmation and investigation.…”
mentioning
confidence: 99%
“…Golgin45 was also demonstrated to interact with DNA (cytosine-5)-methyltransferase 3-like protein DNMT3L and AP-1 (9,10). Gene profile analysis found that Golgin45 expression was up-regulated in liver cells that responded to dengue virus infection (11), in transcription factor Gfi-1B (growth factor independence 1B) overexpressing leukemia cells (12), and in EBLN1 (Endogenous bornavirus-like nucleoprotein elements) silencing oligodendroglia cells (13), and it was reduced in hepatocellular carcinoma tissues (14). The exact role of Golgin45 still needs further confirmation and investigation.…”
mentioning
confidence: 99%
“…Because no natural selection of hsEBLN-1 and its orthologues is detected [54], hsEBLN-1 is thought to function as a DNA element or non-coding RNA, or even to have lost its function (Figure 3). He et al reported that 1067 and 2004 genes are up-and downregulated, respectively, after knockdown of hsE-BLN-1 RNA in human oligodendroglia cells [55]. The top 10 most upregulated genes were PI3, RND3, BLZF1, SOD2, EPGN, SBSN, INSIG1, OSMR, CREB3L2, and MSMO1, and the top 10 most downregulated genes were KRTAP2-4, FLRT2, DIDO1, FAT4, ESCO2, ZNF804A, SUV420H1, ZC3H4, YAE1D1, and NCOA5.…”
Section: Gene Regulation By Ebln Rnasmentioning
confidence: 99%
“…The top 10 most upregulated genes were PI3, RND3, BLZF1, SOD2, EPGN, SBSN, INSIG1, OSMR, CREB3L2, and MSMO1, and the top 10 most downregulated genes were KRTAP2-4, FLRT2, DIDO1, FAT4, ESCO2, ZNF804A, SUV420H1, ZC3H4, YAE1D1, and NCOA5. Gene ontology revealed that hsEBLN-1 may regulate the expression of genes related to the cell cycle, the mitogen-activated protein kinase pathway, p53 signaling, and apoptosis [55].…”
Section: Gene Regulation By Ebln Rnasmentioning
confidence: 99%
“…Найчастіше це філовіруси (зокрема, вірус Ебола) та борнавіруси (вірус хвороби Борна). Одним із можливих механізмів реалізації цих ендогенних борнавірусів може бути їх роль у регуляції функцій клітини, її неконтрольованого розмноження (проліферації) та загибелі (апоптозі) (He et al, 2016). Адже саме борнавіруси мають унікальну здатність інтегруватися у процесі своєї реплікації в геном господаря, тому автори припускають набагато ширше коло природних господарів цих вірусів, а їх біологічне значення потребує подальшого вивчення.…”
Section: значення борнавірусів у патології людиниunclassified